En qué cambian los pacientes drogodependientes a los seis meses de tratamiento en la comunidad terapéutica. - Pórez del Río, Fernando (Revista de la Asociación Española de Neuropsiquiatría, 2012)
Introduction. The aim of this study is to show how patients who are dependent on drugs change after six months' treatment in the Therapeutic Community (TC). Material and methods. Eight diagnostic tests were Performed after the first month and after six months' treatment, pre test and post test design. The ques- tionnaires used were: EuropASI. Psychopathology Questionnaire (SCL- 90-R). Aggression Questionnaire (AQ). Personality Disorders (IPDE). Self-Efficacy Questionner (SES). Change Assessment Scale (URICA). Process of Change Questionnaire (PCQ). Decisional Balan- ce Questionnaire (DBC). 76 patients in the TC diagnosed as dependent on subs- tances were assessed according to DSM IV-TR. In order to carry out the socio-demographic profile and &+(#*(,'!.*)(**#&!#%--'0&'!)#$,!?7(B#'&#"%*#%00!3$7'*- hed an analysis of Conglomerate in two phases with the data resulted in EuropASI. The average age of the participants was 33 years (range: 22-56 years). For the rest of the questionnaires, the dependent variables Were classified in Z-scores and analyses of variance were then performed with repeated avera- ges (ANOVA). Results and conclusions. The requirements were met for maintaining that there are significant changes in the following variables that were studied: (a) they do not consume substances; (b) they progress to the Action phase; (c) there are changes in the Decisional Balance; (d) their Self-Efficacy increase; (e) there are changes to the Hostility variable; (f) There are increases in five Change Processes. .